PERSEPSI APARATUR DESA TERHADAP PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP PARTISIPASI MASYARAKAT DI DESA NIFUBOKE KECAMATAN NOEMUTI KABUPATEN TIMOR TENGAH UTARA - Bernadetha Bakun Fallo; Marthen Patiung; Aplonia Pala; Maria Kristiyanti Napa; Sidelfi Olfia Bengu (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2026)
This study aims to analyze the influence of village head leadership on community participation in development in Nifuboke Village, Noemuti District, North Central Timor Regency, based on the perceptions of village officials. Village head leadership is considered an important factor in encouraging community involvement in village development processes, including planning, implementation, and supervision stages. This study employed a quantitative approach using a survey method. The research population consisted of 13 village government officials in Nifuboke Village, all of whom were selected as respondents through a saturated sampling technique. Data were collected through questionnaires, observation, and documentation. Data analysis included validity and reliability tests, simple linear regression, coefficient of determination, and hypothesis testing using SPSS version 28. The findings indicate that village head leadership has a positive and significant influence on community participation in village development. The regression results demonstrate that improved leadership quality is followed by increased community participation. The coefficient of determination indicates that village head leadership contributes substantially to variations in community participation, while the remaining proportion is influenced by other factors beyond the scope of this study. These findings emphasize the importance of communicative, participatory, and responsive leadership in strengthening community engagement in village development.